Semi Fowler Position Adjustment to Treat Ventilation Disorders In Post Craniotomy Meningioma Patients - Fidha Fairuz Syafira; Adiratna Sekarsiwi (MBUnivPress, 2022)
Meningiomas are one of the most common types of brain tumors. Interventions that can be done in cases of meningiomas are craniotomy, which is a surgical procedure performed by opening a portion of the skull bone to access the brain directly, and this will be directly related to the nerves. Impaired spontaneous ventilation is the most common problem and if it does not get treatment quickly it will be fatal, namely death. The method used in this research is descriptive with a case study approach. The results showed that after setting the semi-Fowler's position in post-craniotama patients for three days, the patient's condition had not changed, which could be seen from the absence of changes in ventilation disturbances seen from the absence of an increase in patient awareness. In conclusion, the application of semi-Fowler's position adjustment has not been able to overcome ventilation disorders that occur in post-craniotomy patients. This may be influenced by the patient's condition.